The development and evaluation of effective reading programmes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University - Wong, Connie Shiuk Hien (Massey University, 1982)
Theoretical constructs of reading and learner-controlled instruction were used to develop an Effective Reading Programme. Based on these concepts, instrument and non-instrument based techniques were applied to achieve its objectives. Evaluation of the Effective Reading Programme was conducted through an Evaluation model, comprised of Theoretical Constructs, Programme Design and Programme Results. The six stages of its development were individually described and evaluated, moving from courses conducted in South Africa, to those conducted in New Zealand. The conclusion at the end of its developmental stages, was a professional programme, which offered a guarantee within its results. Implications and recommendations were made for areas of further investigation.
Keywords: Reading